2019
DOI: 10.1080/21691401.2019.1617727
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Upregulation of long non-coding RNA OGFRP1 facilitates endometrial cancer through regulating miR-124-3p/SIRT1 axis and activating PI3K/AKT/GSK-3β pathway

Abstract: We planned to investigate the possible influences of long non-coding RNA (opioid growth factor receptor pseudogene 1) OGFRP1 in endometrial cancer and its potential regulatory mechanism. We measured the level of OGFRP1 in endometrial cancer tissues and evaluated the influences of OGFRP1 dysregulation on the tumour cell biological processes of endometrial cancer cells. Further, the regulatory relationships between OGFRP1 and miR-124-3p, between miR-124-3p and Sirtuin1 (SIRT1) were, respectively, investigated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…The expression level of OGFRP1 was significantly upregulated in endometrial cancer . Lv et al (2019) also experimentally confirmed that knockdown of OGFRP1 suppressed the malignant behaviors of endometrial cancer, including suppressed cell viability, enhanced cell apoptosis and inhibited cell migration and invasion. OCT4-pg5 was found to be aberrantly activated in endometrial cancer samples compared with benign endometrium samples, and increased expression of OCT4-pg5 enhanced proliferation by promoting OCT4/PI3K/AKT/CCND1 signaling (Bai et al, 2015).…”
Section: Endometrial Cancermentioning
confidence: 67%
“…The expression level of OGFRP1 was significantly upregulated in endometrial cancer . Lv et al (2019) also experimentally confirmed that knockdown of OGFRP1 suppressed the malignant behaviors of endometrial cancer, including suppressed cell viability, enhanced cell apoptosis and inhibited cell migration and invasion. OCT4-pg5 was found to be aberrantly activated in endometrial cancer samples compared with benign endometrium samples, and increased expression of OCT4-pg5 enhanced proliferation by promoting OCT4/PI3K/AKT/CCND1 signaling (Bai et al, 2015).…”
Section: Endometrial Cancermentioning
confidence: 67%
“…Numerous studies have shown that microRNAs play a crucial part in regulating cancer cell apoptosis, proliferation, invasion, growth, and metastasis [23][24][25][26][27]. Therefore, we made a further exploration of whether SFTPC downregulation in lung cancer was mediated by microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-629-3p was upregulated in LUAD and a potential negative regulator to SFTPC MicroRNAs, a type of endogenous small molecule non-coding single-stranded RNAs, display a repressive effect on target gene expression or mRNA degradation [23,24]. Mountains of evidence show that microRNAs play crucial parts in regulating malignant cell apoptosis, proliferation, invasion, growth and metastasis [23][24][25][26][27]. Herein, we explored whether SFTPC expression was modulated by microRNAs in lung cancer.…”
Section: Sftpc Regulated Luad Cell Proliferation In Vitro and Tumour mentioning
confidence: 99%
See 1 more Smart Citation
“…33 On the contrary, SIRT1 was proved to promote tumor development in breast cancer and endometrial cancer. 34,35 Alves-Fernandes et al suggested that the contradictory role of SIRT1 might due to the different cell type and SIRT1 localization. 36 A previous study revealed that SIRT1 promoted HBV replication in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%